PENGARUH PERCEIVED QUALITY, PERCEIVED RISK TERHADAP CUSTOMER TRUST DENGAN STORE IMAGE SEBAGAI VARIABEL MEDIASI PADA KONSUMEN SAYURAN ORGANIK MEREK FRESHARVEST DI KOTA BANDA ACEH - Agung Ade Yanuar Bulan; Sorayanti Utami (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
The aim from research this is for knowing the effect of perceived quality, perceived risk on customer trust with image store as variable mediation . Research this do at 100 consumers at Suzuya Mall Banda Aceh. Retrieval sample use non probability sampling method . Research this use four variable , i.e. variable free , variable bound and variable mediation . Method analysis Hierarchical Linear Modeling (HLM) used as method analysis for knowing influence between variable free with variable bound . Questionnaire   be measured use Likers Scale . Test validity , reliability , normality , and analysis regression use SPSS Statistics 20 . Results showing perceived quality have influence positive to customer trust; perceived risk have influence negative to customer trust ; perceived quality have influence positive to store image ; perceived risk have influence negative to store image; store image have influence positive to customer trust; store image mediate relationship between perceived quality and customer trust; store image  mediate relationship between perceived risk and customer trust.